2020
DOI: 10.1016/j.asmr.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Which Metrics Are Being Used to Evaluate Children and Adolescents After ACL Reconstruction? A Systematic Review

Abstract: Purpose To identify a comprehensive list of outcome measures previously used in the literature to evaluate clinical outcomes after reconstruction of the anterior cruciate ligament (ACL) in patients 18 years of age or younger. Methods A literature search was performed by querying MEDLINE, Embase and Cochrane computerized databases for relevant articles that reported clinical outcomes in pediatric patients undergoing ACL reconstruction. Studies that were nonclinical, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 126 publications
0
12
0
Order By: Relevance
“…This survey has been extensively used in the literature, [11][12][13][14][15] and a recently published systematic review showed that Pedi-IKDC is the most studied PROM and has the best psychometric properties and, as such, should be preferred in detriment of other instruments. 12 The Pedi-IKDC was already validated in many other languages, [15][16][17] with the validation studies being conducted in pediatric populations affected by a broad spectrum of knee injuries and disorders. However, to date there were no knee-specific PROMS validated for the Portuguese-speaking pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…This survey has been extensively used in the literature, [11][12][13][14][15] and a recently published systematic review showed that Pedi-IKDC is the most studied PROM and has the best psychometric properties and, as such, should be preferred in detriment of other instruments. 12 The Pedi-IKDC was already validated in many other languages, [15][16][17] with the validation studies being conducted in pediatric populations affected by a broad spectrum of knee injuries and disorders. However, to date there were no knee-specific PROMS validated for the Portuguese-speaking pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…In adults, a weak to moderate correlations between functional tests (including strength tests) and the International Knee Documentation Committee (IKDC) questionnaire and Tegner score has been reported 6–9 months after ACL reconstruction [26]. It is unknown if these relations between outcomes exist in children with ACL injury, and only about 15% of studies on treatment of ACL injury in children include functional tests [27], 39], and generally there is no standard for how outcomes are best reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…87 Fabricant found the use of PROMs to evaluate pediatric ACLR is neither standardized nor validated for the population. 88 The Lysholm, International Knee Documentation Committee Subjective Knee form (IKDC), Tegner Activity Scale, and Knee Injury and Osteoarthritis Outcome Score (KOOS) are frequently reported PROMs in the pediatric ACL literature, 88,89 but none are designed for nor validated in the pediatric population. The use of adult PROMs in children has been shown to cause comprehensibility problems and should be avoided.…”
Section: Return To Sport Testing For the Youthmentioning
confidence: 99%